Extradition Arrangements in Efforts to Eradicate Corruption Crimes in Indonesia - Sulaiman Rasyid; Joko Setiyono (Jurnal Dinamika Hukum, 2021)
Corruption is a serious threat to the stability and security of the state and the international community and has weakened institutions, democratic values and justice. This article discusses extradition arrangements in Indonesian law and discusses efforts to eradicate corruption through extradition agreements. In conducting this research, this research uses a literature study research method. The results of this study are extradition can be carried out based on an agreement and if there is no agreement between the two countries, then extradition can be carried out on the basis of good relations between countries. If there is no previous extradition treaty between the requesting country and the requested country, the requesting country can request arrest through INTERPOL. In terms of returning assets resulting from corruption, there is a Mutual Legal Assistance in Criminal Matters (MLA) mechanism that can be applied this is because corruption is considered a serious crime and this crime is transnational in nature so it requires cooperation between countries to eradicate it.Keywords: extradition; corruption; serious crimes; law enforcement